Rethinking the role of phosducin: Light-regulated binding of phosducin to 14-3-3 in rod inner segments - Nakano, Koichi (National Academy of Sciences, 2001)
Phosducin (Pd), a small protein found abundantly in photoreceptors, is widely assumed to regulate light sensitivity in the rod outer segment through interaction with the heterotrimeric G protein transducin. But, based on histochemistry and Western blot analysis, Pd is found almost entirely in the inner segment in both light and dark, most abundantly near the rod synapse. We report a second small protein, 14-3-3, in the rod with a similar distribution. By immunoprecipitation, phospho-Pd is found to interact with 14-3-3 in material from dark-adapted retina, and this interaction is markedly diminished by light, which dephosphorylates Pd. Conversely, unphosphorylated Pd binds to inner segment G protein(s) in the light. From these results and reported functions of 14-3-3, we have constructed a hypothesis for the regulation of light sensitivity at the level of rod synapse. By dissociating the Pd/14-3-3 complex, light enables both proteins to function in this role.